Peran Organisasi dan Komunikasi bagi Pimpinan di Lingkungan Kerja - Rima Rizki Syahputri; Suhairi Suhairi; Sri Aderafika Sani; Soibatul Aslamia Nasution (Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
This study aims to determine the role of organizational communication for leaders in the work environment. Communication activities within an organization aim to establish mutual understanding and equate experiences among members of the organization. With good communication, an organization can run smoothly. On the other hand, lacking or absent communication, organizations can fall apart. Therefore, leadership in organizational communication is very important because the presence of the leader is one of the spearheads of success in the organization. The results of the study concluded that communication in a leadership is a very important element in achieving the success of the goals to be achieved by an organization. Therefore, a leader should be good at communicating both verbally and non-verbally. Good communication will be able to increase motivation, so that the information conveyed can be well received and this will be able to improve performance and work control will also be carried out properly. In an organization the leader is a communicator. Effective leaders generally have effective communication skills, so that more or less will be able to stimulate the participation of the people they lead.